2023
DOI: 10.1002/cam4.5752
|View full text |Cite
|
Sign up to set email alerts
|

Planning for return to work during the first year after breast cancer metastasis: A Swedish cohort study

Abstract: Background Planning for return to work (RTW) is relevant among sub‐groups of metastatic breast cancer (mBC) survivors. RTW and protective factors for RTW in patients with mBC were determined. Methods Patients with mBC, ages 18–63 years, were identified in Swedish registers, and data were collected starting 1 year before their mBC diagnosis. The prevalence of working net days (WNDs) (>90 and >180) during the year after mBC diagnosis (y1) was determined. Factors associated with RTW were assessed using regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Research studies have shown that brain metastasis, secondary to breast cancer, can impact occupational functioning, as patients may experience physical and psychological symptoms that affect their ability to work. For example, a study by Johnsson et al (2023) found that breast cancer survivors with metastatic disease reported greater impairments in work ability and productivity among other daily activities compared to those without metastasis. Although research has shown that occupational therapy interventions can significantly improve the QoL for patients with symptoms of brain metastasis, secondary to breast cancer, by addressing physical, cognitive, and emotional needs (Fleege et al, 2023), occupational therapy has remained underused (Pergolotti et al, 2016).…”
mentioning
confidence: 99%
“…Research studies have shown that brain metastasis, secondary to breast cancer, can impact occupational functioning, as patients may experience physical and psychological symptoms that affect their ability to work. For example, a study by Johnsson et al (2023) found that breast cancer survivors with metastatic disease reported greater impairments in work ability and productivity among other daily activities compared to those without metastasis. Although research has shown that occupational therapy interventions can significantly improve the QoL for patients with symptoms of brain metastasis, secondary to breast cancer, by addressing physical, cognitive, and emotional needs (Fleege et al, 2023), occupational therapy has remained underused (Pergolotti et al, 2016).…”
mentioning
confidence: 99%